In0.17Al0.83N/AlN/GaN triple T-shape Fin-HEMTs with gm=646 mS/mm, ION=1.03A/mm, IOFF=1.13 μA/mm, SS=82 mV/dec and DIBL=28 mV/V at VD=0.5 V - Teo, Khoon Leng (2015)
We report the first 3D Triple T-gate InAlN/GaN nano-channel (NC) Fin-HEMTs on Si substrate with record high device performances at VD as low as 0.5 V. Utilizing a T-gate approach on NC Fin-HEMT with stress engineered techniques, enhanced device transport properties with gm=646 mS/mm, Ion=1.03 A/mm, IOFF=1.13 μA/mm, ION/IOFF~106, SS=82 mV/dec at VD=0.5 V were achieved. In addition, the Fin-HEMT also exhibited 3.2 times lower DIBL of 28 mV/V. The dramatic improvement of device performance is due to the tensile stress induced by SiN passivation in the NC Fin-HEMT.